A molecular and morphological investigation into the origins of Ligustrum × vicaryi (Oleaceae) with consideration of its nomenclature. (September 2015) - Edwards, D.; Griffin, J. H. C.; Armitage, J. D.
Abstract : A combined molecular and morphological study was employed to investigate the origins of Ligustrum ×  vicaryi, reportedly a hybrid between the introduced L. ovalifolium and the British and Irish native L. vulgare . Two DNA regions, the nuclear ribosomal internal transcribed spacer region (ITS) and the chloroplast psb A– trn H intergenic spacer region were sequenced. In total, 109 accessions, including wild-collected and garden plants, were sampled representing 21 of the 22 species in cultivation in Britain and Ireland. Neither DNA sequence data nor morphology implicates L. vulgare in the parentage of L . ×  vicaryi ; instead it is very likely to be the result of a cross between two individuals of L. ovalifolium with different genotypes. Nomenclatural considerations are discussed and the adoption of the name L. ovalifolium 'Vicaryi' is advocated. The character of glabrous shoots often used to separate L. ovalifolium from L. vulgare is rejected and a clearer characterisation presented. The importance of research-led data-gathering when considering interactions between native and non-native plants is emphasised.